Impact of Micro-Finance on Business Creation: A Case of Nepal - Dhungana, Bharat Ram (Journal of Nepalese Business Studies, 2018)
The paper examines the impact of micro-finance on business creation in Nepal through paired sample t-test, chi-square test and Wilcoxon signed rank test. The research is based on primary data collected through structured questionnaires. The survey includes 500 micro-finance clients from four districts of western development region who have been involved in micro-finance programme for last five years. There is a positive association between loan size and its application. The clients who have taken small size of loans, they have mostly spent their loans on domestic purposes and found poor application of loans in micro-business whereas big loan size clients have greater application of loans in productive sectors. The study concludes that micro-business and enterprises creation of people have been significantly improved after involvement in micro-finance programme. Micro finance institutions should give equal priority for non-financial services such as financial literacy and provision of entrepreneurship skills through government and non-government organizations that ultimately helps to utilize micro-credit into productive sectors.